LONG LIFE EDUCATION DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Nuryaumin, Nuryaumin (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2020)
National Education aims to develop abilities and shape the character and civilization of a nation with dignity in the context of educating the nation's life, aiming to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent , and become a democratic and responsible citizen. Whereas in Islam, ordering high morals is the goal in Islamic education. And education must be formally conceptualized as a continuous process in individual life, from early childhood to adulthood, so that it is able to become a shield which is at the same time used as a filter and also used as a guide and behavior for adolescents to be used as a shield in facing the challenges of the times. . The concept of life education is the ability of those in charge of education in educating their students, because of their abilities. The responsibility for education, among others, is borne by parents as household educators, teachers (educators) as those in charge of education in schools and community leaders as those in charge of education in society. The concept of Islamic religious education in realizing life education is the need for association which is an environment that participates in educating someone.